The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1093/molehr/gau016
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia inducible factor 2α/insulin-like growth factor receptor signal loop supports the proliferation and Oct-4 maintenance of mouse germline stem cells

Abstract: Hypoxia inducible factor 2α (HIF-2α) is critical for primordial germ cell (PGC) survival as knockout of HIF-2α (HIF-2α(-/-)) decreases both expression of Oct-4 and PGC number in genital ridge. Hypoxia is known to stabilize HIF-2α protein from proteasomal degradation. However, little is known about the hypoxia-associated endocrinal signaling in HIF-2α expression. The current work demonstrates a role for an endocrine insulin-like growth factor-I receptor (IGF-IR)-PI3K/Akt-mTOR-HIF-2α regulatory loop in the proli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(36 citation statements)
references
References 34 publications
3
33
0
Order By: Relevance
“…It could be induced by spheroidal structure and high-density culture gel environment. We have learned that the spheroid center has a lower oxygen tension than the outer layers 10, 14 , and hypoxia can mediate or regulate the expression of NANOG and OCT-4 3436 . In HA ASC spheroids, we found a NANOG-negative surface zone and a NANOG-positive core zone of spheroids (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…It could be induced by spheroidal structure and high-density culture gel environment. We have learned that the spheroid center has a lower oxygen tension than the outer layers 10, 14 , and hypoxia can mediate or regulate the expression of NANOG and OCT-4 3436 . In HA ASC spheroids, we found a NANOG-negative surface zone and a NANOG-positive core zone of spheroids (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, T is known to promote the generation of PGCs (Aramaki et al, 2013). Other Rhox10 -regulated genes encode factors driving ProSG/SSC proliferation and/or survival, including Erbb3 , which encodes a receptor tyrosine kinase that has been implicated in driving ProSG proliferation (Toyoda-Ohno et al, 1999) and Epas1 , which encodes a hypoxia-induced transcription factor that supports proliferation of germline stem cell cultures (Huang et al, 2014). …”
Section: Discussionmentioning
confidence: 99%
“…Specifically, nuclear IGF1R interferes with Wnt signaling, which upregulates ABC drug transporters and modulates drug responses (99). Regarding the tumor microenvironment, activating IGF1R results in stabilizing hypoxia-inducible factor (HIF)-1α and HIF-2α, and the upregulation of vascular endothelial growth factor (100). A previous study demonstrated that overexpressing HIF-1α increased the expression of Bcl-2, decreased the expression of BAX, and induced the expression of MDR1 and MRP1 (101).…”
Section: Interacting With Ecmmentioning
confidence: 99%